2017
DOI: 10.1007/s12253-017-0364-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between Polymorphisms of X-Ray Repair Cross Complementing Group 1 Gene and Pancreatic Cancer Risk: a Systematic Review with Meta-Analysis

Abstract: Emerging evidences have shown that common genetic polymorphisms in X-ray repair cross complementing group 1 (XRCC1) gene may be associated with the development of pancreatic cancer, but individually published studies and previous meta-analyses revealed inconclusive results. The aim of our study was to investigate the association between polymorphisms in XRCC1 gene and pancreatic cancer risk. We conducted a search of PubMed, Embase, the Cochrane Library and Web of Science databases. Odds ratios (ORs) with 95% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…34 , 35 The association of rs1799782 with cancer risk remains controversial. Some previous studies have reported a significant association of rs1799782 with thyroid cancer, 16 colorectal cancer, 19 lung cancer, 17 and cervical cancer, 18 while no significant association could be observed with breast cancer, 36 pancreatic cancer, 37 and gastric cancer. 15 rs25487 and rs25489 polymorphisms are another widely studied polymorphism with evidences supporting a quantitative effect of the genotype on the phenotype.…”
Section: Discussionmentioning
confidence: 89%
“…34 , 35 The association of rs1799782 with cancer risk remains controversial. Some previous studies have reported a significant association of rs1799782 with thyroid cancer, 16 colorectal cancer, 19 lung cancer, 17 and cervical cancer, 18 while no significant association could be observed with breast cancer, 36 pancreatic cancer, 37 and gastric cancer. 15 rs25487 and rs25489 polymorphisms are another widely studied polymorphism with evidences supporting a quantitative effect of the genotype on the phenotype.…”
Section: Discussionmentioning
confidence: 89%
“…APEX1 polymorphism has been reported to be associated with the efficacy of platinum-based adjuvant chemotherapy on cervical cancer ( Chung et al, 2006 ) and non-small cell lung cancer ( Pérez-Ramírez et al, 2019 ). In addition, it may increase the risk of other cancers, such as breast cancer ( Mitra et al, 2008 ), colorectal cancer ( Wang L. et al, 2016 ) and pancreatic cancer ( Chen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%